Radiacja autobiografizmu w twórczości Zofii Kossak = Radiation of autobiographism in the works of Zofia Kossak - Heck, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Autobiographical works by Zofia Kossak-Szczucka (Szatkowska) (1899-1968) is characterised in the background of the modern identity narrations by "radiation", radiation of autobiographism, i.e. an autobiography extended by a history of the family, including autobiographical motifs in various generic forms of fictitious prose. What stands out is also the creation of webs of autobiographical and memory narrations by memoirs of ancestors, descendants, relatives and in-laws of the writer.
Keywords: autobiografizm; autobiografia; biografia; wspomnienia; doświadczenie; autobiographism; autobiography; biography; memoirs; experience